Application of Altman Z-Score Model and Springate Model to Assess the Symptoms of Corporate Banking (Analysis of Studies in Consumer Companies in the Pharmaceutical Sub Sector Registered on the Indonesia Stock Exchange during the 2014-2017 Period) - Asep Saepudin; Soritaon Siregar (Journal of International Conference Proceedings (JICP), 2019)
The purpose of this study was to examine differences in predictions of symptoms of corporate bankruptcy between the Altman Model and the Springate Model against the symptoms of bankruptcy in the Manufacturing Sector of the Pharmaceutical Sub-sector listed on the Indonesia Stock Exchange during the 2014-2017 period. The research method used is descriptive method. The population in this study were all publicly listed companies on the Indonesia Stock Exchange in 2014 to 2017. Sampling techniques with use of purposive sampling. Based on the sampling criteria, obtained a research sample of 9 pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange during the 2014-2017 period. From the results of the study, the difference between the two is the ratio of the capital market value to the book value of the debt owned by the Altman equation, not owned by the Springate equation. This ratio has a very significant effect because stock prices contribute to the results of the Altman Z-Score model.